Comparison of irrigation techniques on enterococcus faecalis reduction: in vitro study - Janwattanavej, Sirikan; Ongchavalit, Lalida; Laovanitch Srisatjaluk, Ratchapin (Mahidol Dental Journal, 2020)
Objectives: To evaluate and compare the antibacterial efficacy of needle irrigation, passive ultrasonic irrigation technique (PUI) and continuous ultrasonic irrigation technique (CUI) in molar teeth. Materials and methods: The mesial roots of 35 mandibular molars were instrumented in a crown-down manner with K3 nickel titanium files to achieve a master apical file size 35/.04. All root canals were contaminated with Enterococcus faecalis . The initial bacteriologic samples were collected from all teeth before irrigation. Specimens were randomly assigned to 3 experimental groups: group 1 NaOCl/needle irrigation, group 2 NaOCl/PUI, and group 3 NaOCl/CUI. Bacteriologic samples were collected immediately after irrigation. The percentages of bacterial reduction from 3 experimental groups were compared (p-value <.05) Results: There was a significant difference in the percentages of bacterial reduction between three experimental groups. The PUI group showed the percentage of bacterial reduction greater than the CUI group, however the percentage of bacterial reduction of needle irrigation group was not significantly different from PUI and CUI groups. Conclusions: All irrigation techniques could reduce a number of bacteria from contaminated root canals. The PUI group produced greater antimicrobial efficacy than the CUI group.